An exploratory study to evaluate the teaching strategies in the hybrid Higher Education classroom - van Wyk, H.; Rosa, C. (South African Journal of Higher Education, 2024)
This article presents the findings of a South African study conducted in a private Higher Education Institution. The aim of the article was to explore teaching strategies suitable for hybrid classrooms, to create an environment to integrate virtual and in-person student groups for optimal learning outcomes. A hybrid classroom requires academic staff to engage both groups in student-centred activities and therefore, this article argues that traditional teaching strategies may not be optimal in achieving integration. This exploratory study employed a practical action research design, to teaching strategies in hybrid classrooms. The data was collected by conducting class observation and two focus groups. The study used Braun and Clarke’s (2006) thematic analysis for data analysis. The findings indicated that academic staff have a limited understanding regarding teaching strategies that would bridge the gap between virtual and in-person students. The study emphasised the necessity of an inquiry-based mindset in the hybrid teaching environment. The focus groups unanimously advocated for adopting an “adapted student-centred instructional approach” to address hybrid classroom challenges. This research contributes to understanding student-centred teaching strategies in hybrid classrooms. The key insight was that teacher-centred approaches by academic staff did not equally integrate virtual and in-person student participation. The study underscores the importance of lecturer training in effective student-centred teaching strategies for optimal learning in hybrid classrooms